A Nomadic Diagram: Waddington's Epigenetic Landscape and Anthropology. Issue 4 (1st December 2019) - Humphrey, Caroline
Abstract : The idea of the diagram as a 'working object' is used to discuss the biologist C. H. Waddington's epigenetic landscape (EL) diagrams. This article investigates the diagrams' history and discusses their usages in relation to Stengers's idea of the 'nomadic concept'. What is it about these diagrams that have made them a tool for transdisciplinary research? The article argues that it is useful to distinguish between the diagram and the illustration, and that it is in part because the EL diagrams retain an illustrative graphic character that they have been apt for imaginative adaptation and reuse. The diagram in this case becomes an 'ontological go-between' that is thereby able to function in different contexts, such as sociology and anthropology.